Kepemimpinan Kepala Sekolah Perempuan Berbasis Gender - Andi Tenri Abeng; Faridah Faridah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study examines the leadership of gender-based female principals at the primary school level in Barebbo Sub-district, Bone Regency, South Sulawesi. The purpose of this study is to describe how gender-based principal leadership is based on the character and context of leadership. The study was adopted from the Gender and Leadership approach based on the FourC-PITO concept. Character is an individual trait or personality and the values that a person believes in. Character in educational leadership relates to self-confidence, independence, responsibility, gender stereotypes, interpersonal relationships, and team management. Context is the physical, psychological, social, economic environment and various situations. Context in leadership is related to stress management, differences in gender relations, socio-cultural conditions, the number of human resources, and work status. The sampling methodology used purposive sampling with informants as many as 5 female principals. This research uses a qualitative descriptive method. The research data were obtained using interviews, observation and documentation. Checking the validity of the data using triangulation techniques. The results showed that: (1) The leadership character of elementary school principals in Barebbo Subdistrict, Bone Regency, generally has confidence, is responsible, open to other people's ideas, maintains interpersonal relationships, is democratic, and has good management. (2) The most prominent contexts for gender-based principal leadership are educational strata, gender equality, family relationships, number of resources, work status, regional origin, and teacher adaptability. Keywords: gender, female principal, leadership Abstrak: Penelitian ini mengkaji tentang kepemimpinan kepala sekolah perempuan berbasis gender jenjang SD Kecamatan Barebbo, Kabupaten Bone, Sulawesi Selatan. Tujuan penelitian ini yaitu mendeskripsikan bagaimana kepemimpinan kepala sekolah berbasis gender berdasarkan karakter dan konteks kepemimpinan. Kajian tersebut diadopsi dari pendekatan Gender and Leadership yang berdasar pada konsep FourC-PITO. Karakter merupakan sifat individu atau kepribadian dan nilai-nilai yang diyakini seseorang. Karakter berkaitan dalam kepemimpinan pendidikan berkaitan dengan kepercayaan diri, kemandirian, tanggung jawab, stereotip gender, hubungan interpersonal, dan pengelolaan tim. Konteks merupakan lingkungan fisik, psikologis, sosial, ekonomi, dan berbagai situasi. Konteks dalam kepemimpinan berkaitan dengan pengelolaan stres, perbedaan relasi gender, kondisi sosial budaya, jumlah SDM, hingga status kerja. Metodologi pengambilan sampel menggunakan purposive sampling dengan informan sebanyak 5 kepala sekolah perempuan. Penelitian ini menggunakan metode deskriptif kualitatif. Data hasil penelitian diperoleh dengan menggunakan wawancara, observasi dan dokumentasi. Pengecekan keabsahan data menggunakan teknik triangulasi. Hasil penelitian menunjukkan bahwa: (1) Karakter kepemimpinan kepala sekolah SD di Kecamatan Barebbo Kabupaten Bone pada umumnya memiliki kepercayaan diri, bertanggung jawab, terbuka terhadap gagasan orang lain, menjaga relasi interpersonal, demokratis, dan memiliki manajemen yang baik. (2) Konteks yang paling menonjol pada kepemimpinan kepala sekolah berbasis gender berupa, strata pendidikan, kesamaan gender, hubungan kekeluargaan, jumlah sumberdaya, status kerja, asal daerah, dan kemampuan adaptasi guru. Kata kunci: gender, kepala sekolah perempuan, kepemimpinan